(untitled) (International Journal of Physiotherapy, 2018)
Background: Several studies have evaluated the effects of knee osteoarthritis on general and specific activities of the population using various health-related questionnaires in their original/native form, but very few have reported in Saudi Arabian population using Arabic versions. The target of the study is to observe the degree of knee difficulties during pivoting, kneeling and squatting in bilateral knee osteoarthritis male patients using disease-specific Arabic Version Knee injury and osteoarthritis outcome score physical function (KOOS-PS) short form questionnaire in Saudi Arabian population. Methods: A cross-sectional study exploring 109 male primary bilateral knee osteoarthritis patients in Saudi Arabia. Subjects were assigned to three different groups based on their age after meeting the American College of Rheumatology criteria. Demographic data were obtained, and subjects were asked to rate their degree of knee difficulty during pivoting, kneeling and squatting activities using the disease-specific Arabic short-form questionnaire. Results: The statistical description introduced in the mean, standard deviation, median, 95% confidence interval (95% CI). The statistical parameters such as mean and standard deviations were 84.08±8.81, 76.58±11.49, 28.05 ± 8.4 in the three age groups such as 50-60, 61 to 70 and above 70 years old along with 95% confidence intervals 78.2-84, 72.6-80.47, and 25.17-30.94 respectively. The statistical significance found between 50-60years and above 70years p < 0.001, 61-70years and above 70years p < 0.001 but statistical insignificance found between 50-60years and 61-70years age groups p < 0.14. Conclusion: High degree of knee difficulty has been observed in male bilateral knee osteoarthritis during pivoting, kneeling and squatting activities among 61-70years and above 70years of age groups.